ON CYCLIC DECOMPOSITION OF Z-MODULE M_m×r(Z_n) - Ni Wayan Switrayni; I Gede Adhitya Wisnu Wardhana; Qurratul Aini (Diponegoro University, 2022)
A torsion module over a principal ideal domain has special properties related to the way how it is decomposed either into primary or cyclic submodules. This paper carries out a special case of such module over the ring of integer, which consists of all matrices with entries from the set of integer modulo n. The result shows that its decomposition depends on the prime factors of n.